From Dystopic to Decolonial: Reconciling the (In)Determinate Dystopia of Eden Robinson's "Terminal Avenue". Issue 3 (1st December 2020) - Skrynsky, Hannah
Abstract : This paper looks to Haisla-Heiltsuk writer Eden Robinson's short story "Terminal Avenue" (2004) as a literary example of what Canada's future might look like if the collectively felt anxiety that underpins settler society remains unchecked. I analyze "Terminal Avenue" as a work of speculative fiction that represents what I term the genre's "ideology of indeterminacy" as a politically productive condition under which Indigenous/settler relations in contemporary Canada can be reassessed. My analysis builds on the work of settler scholars David M. Higgins and Conrad Scott published in Extrapolation, vol 57, nos. 1–2, 2016.